Ketahanan Industri Mikro dan Kecil: Bukti dari Indonesia - Mukhlis, Mukhlis; Robiani, Bernadette; Bashir, Abdul (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
Micro and small industries (MSIs) play a crucial role in the economy, yet their growth confronts various constraints. This study examines the determinants of Indonesian MSIs output, focusing on the roles of capital, labor, added value, efficiency, and productivity. Panel data from 34 provinces (2013–2023) applied fixed effect model. The findings indicate that capital, labor, added value, efficiency, and productivity have a positive and significant impact on output. Capital’s dominant role highlights the need for improved access to finance. Policies supporting value creation, managerial skills, and technology adoption are crucial to unlocking the MSI potential and ensuring sustainable growth.